Exhibition of Contemporary Paintings from the Sebastian de Ferranti Collection. (Manchester : Whitworth Art Gallery, 1970)
Caulfield, Patrick ; Cook, Roger ; Edwards, John ; Hoyland, John ; Huxley, Paul ; Lancaster, Mark ; Moon, Jeremy ; Riley, Bridget ; Smith, Richard
Exhibition of Contemporary Paintings from the Sebastian de Ferranti Collection, Whitworth Art Gallery - University of Manchester, 5 June to 11 July 1970
boek